1986
DOI: 10.1177/088740348600100403
|View full text |Cite
|
Sign up to set email alerts
|

Imprisoned Elders: The Experience Of One Institution

Abstract: This study examines the characteristics and institutional experience of inmate elders from one medium security institution. It also features a stratified random sample of inmates aged 49 and under from the same institution. Data were collected from inmates files and interviews with inmate elders (aged 50 and older) and institutional staff. Specific attention is given to policy issues concerning the treatment of this special needs group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…In Goetting's (1984a) study, approximately three fourths (74%) were employed prior to incarceration, and the mean completed education level was seventh grade. Wilson and Vito (1986) also found that more than two thirds of the inmates in their sample (from one Kentucky institution) reported less than a high school education. Conversely, there was a greater proportion of high school graduates in studies conducted by Fry (1987) (at one California facility) and by Kratcoski and Babb (1990).…”
Section: Older Inmate Demographicsmentioning
confidence: 85%
See 1 more Smart Citation
“…In Goetting's (1984a) study, approximately three fourths (74%) were employed prior to incarceration, and the mean completed education level was seventh grade. Wilson and Vito (1986) also found that more than two thirds of the inmates in their sample (from one Kentucky institution) reported less than a high school education. Conversely, there was a greater proportion of high school graduates in studies conducted by Fry (1987) (at one California facility) and by Kratcoski and Babb (1990).…”
Section: Older Inmate Demographicsmentioning
confidence: 85%
“…Fewer than half of Federal Bureau of Prisons inmates (n = 2,494, 45%) reported a prior commitment (Kratcoski & Pownall, 1989). Older inmates with criminal justice histories were also prevalent in state-level descriptive studies (Faiver, 1997;Teller & Howell, 1981;Walsh, 1989;Wilson & Vito, 1986).…”
Section: Offenses Committed By Incarcerated Older Offendersmentioning
confidence: 99%
“…The simple "fear of victimization" by younger inmates is also extremely prevalent among elderly inmates. Wilson and Vito (1986) found that inmates housed in a geriatric unit felt vulnerable simply because the most dangerous and unpredictable inmates were held in close proximity.…”
Section: Isolation and Social Needsmentioning
confidence: 99%
“…Older prisoners average three serious health problems, which may include chronic health conditions and substance abuse or dependence problems (Chaiklin & Fultz, 1985; Corrections Today, 1990; Kerbs, 2000a; Marquart, Merianos, & Doucet, 2000; Wilson & Vito, 1986). In a recently published integrative review of health-related research on older prisoners, Loeb and AbuDagga (2006) noted that the most commonly reported health problems included arthritis, back problems, cardiovascular diseases, endocrine disorders, psychiatric conditions, respiratory diseases, sensory deficits (vision and hearing problems), and substance abuse problems.…”
Section: Cost Savings With Centralized Health Carementioning
confidence: 99%